Fit and misfit between ligands and metal ions - Comba, Peter; Schiek, Wolfgang (Coordination chemistry reviews, 2003)
Multidentate and in particular macrocyclic and rigid ligands may enforce a particular structure on a metal complex. Molecular properties, such as stabilities, reduction potentials, reactivities and spectroscopic properties depend on the molecular structures, and molecular properties may, therefore, be tuned by the ligand architectures. Approaches to predict structures and properties will be briefly reviewed and important concepts, including ligand preorganization, complementarity, flexibility, elasticity and energization (entatic states) will be discussed in detail.